The Influence of Financial Literacy, Lifestyle, Income and Locus of Control on Financial Behaviour of The Millenial Generation (Case Studies on Millenial Generation of Master of Management Students at Mercu Buana University) - Arnis Susanti, Anestesia; Aisyah F. Pulungan, Nur (Journal of Accounting and Finance Management, 2025)
In summary, this study examines how lifestyle, income, locus of control, and financial literacy affect financial behavior in a case study of Mercu Buana University's millennial Master of Management students. With a sample size of 120, the study's population consisted of 441 Mercu Buana University Master of Management students. Descriptive analysis and Structural Equation Model Partial Least Square (SEM-PLS) are used in the data analysis procedure. According to the study's findings, financial behavior is positively and significantly impacted by financial literacy, positively and significantly impacted by lifestyle, positively and significantly impacted by income, and positively and significantly impacted by locus of control.